Caring for school-age children - Click, Phyllis (Wadsworth,Cengage Learning, 2012)
This book presents the most pertinent information needed by those involved in after-school programs. Current research has established the importance of quality after-school programs due to their tremendous impact on children's academic achievement, overall happiness, and self-esteem. To address this reality, the new edition presents the latest research and information on school-age child care, and offers numerous practical applications and activities that can be put to use immediately in a child care setting.